Sustainable tourism in small island jurisdictions with special reference of Malta - Briguglio, Lino (2008)
Deals with the delicate balance between the economic benefits and the environmental damage of tourism, with special reference to small island jurisdictions. Assesses the economic and environmental impacts of tourism in Malta. Suggests pre-emptive and corrective measures for the promotion of sustainable tourism.